Cross-border mergers and acquisitions: The importance of local credit and source country finance. (February 2017) - Kandilov, Ivan T.; Leblebicioğlu, Aslı; Petkova, Neviana
Highlights: We study host state and source country credit markets' impact on cross-border M&As in the U.S. States attract a larger number and higher value cross-border M&A deals following interstate banking deregulation. We find a positive impact of source country financial depth on the incidence of cross-border M&As. We uncover a substitution effect between local and source country bank finance. The effects are larger for non-listed firms, cash transactions and for firms that are more dependent on external finance. Abstract: We study host and source country finance and the interplay between the two in determining the incidence and intensity of cross-border mergers and acquisitions (M&As) into the U.S. We find that states adopting interstate banking deregulation attract a greater number and higher total volume of cross-border M&A deals. We also document a positive impact of source country financial depth on the incidence of cross-border M&As and uncover a substitution effect between local and source country bank finance. The effects are larger for deals where cash is used as the method of payment as well as for firms that are more dependent on external finance, and smaller for publicly traded firms.